Pentingnya Pengembangan Kecerdasan Naturalis Pada Anak Usia Dini di RA An-Nur - Fauziah Nasution; Fadhila Husna; Melvi Sari Anggraini; Rika Nazwa Sabila; Rizka Khairi (CV Edujavare Publishing, 2024)
Naturalistic intelligence is one of the important aspects in the development of early childhood which helps children recognize and understand their natural environment. This article aims to examine the importance of developing naturalistic intelligence through the implementation of contextual learning at RA AN-NUR, Medan. Using the approach of learning about day and night, children are introduced to natural phenomena directly. The results of observations indicate that this method not only strengthens the understanding of basic science concepts but also fosters love and concern for the environment from an early age.